Math Picture Story Media: Its Implementation On Learning Outcomes And Motivation Of Elementary School Students - Managgel, Marlin Blandy; Ramadhani, Widya (Universitas Sembilanbelas November Kolaka, 2023)
This study aims to find the effect of mathematics picture story media on elementary school students' learning outcomes and motivation. This research is a pseudo-experimental research with a post-test-only control group design. Samples were taken randomly from two elementary schools in Saparua District, namely 20 students of SDN 318 Central Maluku (experimental class) and 20 students of SD Kristen Tiouw (control class), with a total sample of 40 students. The research instruments used were the learning outcomes test and motivation questionnaire. The data were normally distributed and homogeneous based on the normality and homogeneity test results. The data obtained were analyzed using a t-test with a t-value of 3.429 2.864 t table and sign. 0.020 (Î± 0,05). The analysis results showed a significant difference in the mathematics learning outcomes of students taught with and without picture story media. At the same time, there is no difference in the learning motivation of students taught with and without picture story media. So there is a significant influence of picture story media on mathematics learning outcomes and student motivation. Another factor that affects student motivation is creating fun learning.